PENGARUH PENGETAHUAN BUSANA DAN ETIKA BERBUSANA TERHADAP PENAMPILAN DI KAMPUS PADA MAHASISWA PKK S1 TATA BUSANA ANGKATAN 2011 FAKULTAS TEKNIK UNIVERSITAS NEGERI SEMARANG - Hawa, Elisatul (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2013)
Clothing is one of the basic human needs as well as the need for food and shelter. Humans have the freedom to dress, but constrained by social norms are ethical. Knowledge and ethical fashion dress dressmaking student S1 PKK is an interesting thing to be studied considering the PKK S1 students have labeled as dressmaking dressmaking teacher candidates. The purpose of this study: to determine the effect of knowledge and ethical fashion dress against PKK student performance dressmaking Force S1 2011 FT UNNES on campus. This study is associative. The study population was all students PKK S1 dressmaking 2011 FT UNNES Force. Engineering samples used in this study is the total sampling technique. Methods of data collection using questionnaires and observation instruments. Analysis of the data using linear regression analysis.The test results obtained Farithmetic F = 60.041 and p value = 0.000. Since the significance value <0.05, we can conclude that Ho is rejected and Ha accepted, so Ha which reads